1,3-Dipolar Cycloadditions of the Versatile Intermediate Tetraethyl Vinylidenebisphosphonate - Ferrer-Casal, Mariana; Barboza, Alejandro P.; Szajnman, Sergio H.; Rodriguez, Juan B. (Synthesis, 2013)
The use of tetraethyl vinylidenebisphosphonate as a dipolarophile in 1,3-dipolar cycloaddition reactions was investigated. In particular, the cycloaddition reactions between tetraethyl vinylidenebisphosphonate and azides and nitrile oxides, and of tetraethyl vinylidenebisphosphonate in the Grigg azomethine 1,3-dipolar cyclization were studied, affording highly functionalized five-membered rings containing the bisphosphonic unit. These straightforward methods allow the preparation of diverse and fairly complex structures bearing the bisphosphonate moiety, which belong to a group of pharmacologically important compounds.
Keywords: bisphosphonates; 1,3-dipolar cycloadditions; azides; nitrile oxides; Grigg azomethine ylides